Malignant prostate cancer in Brazil: morbidity (2013-2018) and mortality (2008-2017) (Research, Society and Development, 2020)
For men, the second type of cancer with the highest incidence and mortality is prostate cancer. The one with the highest incidence is non-melanoma skin cancer and the first cause of mortality is lung cancer. The aim of the study was to elucidate epidemiological data on morbidity and mortality from malignant prostate cancer in Brazil. This is a descriptive, retrospective, epidemiological, historical series, with a quantitative approach, based on secondary data, on morbidity and mortality from malignant prostate cancer, in Brazil. Data on morbidity and mortality due to malignant prostate cancer were obtained in January 2020, in the Brazilian databases: Panel-Oncology and Mortality Information System of the Informatics Department of the Unified Health System (DATASUS). Data on population estimates were obtained from the Brazilian Institute of Geography. The diagnosis of prostate malignancy increased considerably in 2018, an increase of 39.3% between 2017 and 2018. The South and Southeast regions, over the entire period analyzed, have a higher incidence coefficient of malignant prostate cancer than the national coefficient. Regarding mortality from malignant prostate cancer, in the period of 10 years, Brazil registered an increase of 15.6% in this occurrence, reaching 7.4 deaths per 100 thousand inhabitants in 2017. Investment is needed for strategies that guarantee the diagnosis early, through the early detection of malignant prostate cancer.